Apontamentos sobre a função social do direito de propriedade - Campos, Márcio Vergo (2012)
This work aims at retracing the right of ownership not only as an absolute right, mark preserved with the advent of the social function of law. Plays the social function of property as guiding clause of economic destination of property and ordinator of urban, rural and environmental policies, imposing to the owner the power-duty to meet these principles. Seeks to insert the property right into the standard array of economic law and its principled conformation into the constitutional system. The finalistic content of the right to property turns to the generation of wealth not only from the owner, but from society as a whole, based on the supra principle of the human person dignity